Product and geographic scope changes of multinational enterprises in response to international competition - Hutzschenreuter, Thomas; Gröne, Florian (Journal of International Business Studies, 2009)
What happens when multinational enterprises (MNEs) face competition in their own home market from imports or through foreign direct investment (FDI)? We provide a differentiated assessment of the influence of these two types of foreign competition on the product and geographic scope of MNEs. We apply the awareness–motivation–capability framework to international business (IB), hypothesizing that an increase or decrease in scope depends on the motivation and ability of an incumbent firm to respond to an incursion into its home market, and on the objectives and commitment of the firm that is entering that market. We assessed the scope changes of 407 large US firms between 1987 and 2003, and found that increasing imports led to scope reduction, while increasing FDI had the opposite effect. Our analysis of 95 large German firms for the same period led to similar, but somewhat less consistent, results.